ANALISIS CASH TURNOVER DAN RECEIVABLE TURNOVER - Retnosari Retnosari (JIAK : Jurnal Ilmiah Akuntansi dan Keuangan, 2014)
Cash is a medium of exchange that allows management to run its business activities. In fact it is not uncommon that in fact the success of the company to maintain its survival depends on the ability to provide cash to meet financial obligations in a timely manner. Receivables are current assets that are expected to be converted into cash within one year or within one accounting period. Receivables generally arise from the company's core business. However receivables can also result from the presence of the principal outside business activities of the company. Cash and receivables are part or component of working capital so that the velocity of cash and accounts receivable turnover must be considered to achieve high levels of profitability due to higher cash turnover and accounts receivable turnover indicates the shorter the time dependent capital in cash and receivables. This indicates the efficiency in the use of working capital.